Subliminal gait initiation deficits in REM sleep behavior disorder: a harbinger of freezing of gait? - Alibiglou, L. (Mov Disord, 2016)
BACKGROUND: Muscle activity during REM sleep is markedly increased in people with REM sleep behavior disorder (RBD) and people with Parkinson’s disease (PD) who have freezing of gait. This study examined if individuals with RBD, who do not have a diagnosis of PD, show abnormalities in gait initiation that resemble the impairments observed in PD and whether there is a relationship between these deficits and the level of REM sleep without atonia. METHODS: Gait initiation and polysomnography studies were conducted in four groups of 10 subjects each: RBD, PD with and without freezing of gait and control subjects. RESULTS: Significant reductions were seen in the posterior shift of the center of pressure during the propulsive phase of gait initiation in the RBD and PD with freezing of gait groups compared with controls and PD non-freezers. These reductions negatively correlated with the amount of REM sleep without atonia. The duration of the initial dorsiflexor muscle burst during gait initiation was significantly reduced in both PD groups and the RBD cohort. CONCLUSIONS: These results provide evidence that people with RBD, prior to a diagnosis of a degenerative neurologic disorder, show alterations in the coupling of posture and gait similar to those seen in PD. The correlation between increased REM sleep without atonia and deficits in forward propulsion during the push-off phase of gait initiation suggests that abnormities in the regulation of muscle tone during REM sleep may be related to the pathogenesis of freezing of gait.